Application of force-compensating spring modules on mechanical frame of undulators. (1st October 2022) - Chuang, Ping-Shun; Chiang, Hsiao-Wei; Huang, Jui-Che; Kitamura, Hideo; Wang, Pei-Jen
Abstract: A small RMS phase error and long-term stability of the gap-drive system are important criteria for realizing high performance undulators. The use of force compensating spring modules of self-contained type move toward the goals. Since magnetic forces from girders are vanished entirely at the spring module, so not only the small systematic phase error derived from deformation of the girders but also the small dynamic loadings on the mechanical frame and gap-drive system. Moreover, spring modules provide a supplemental mechanism to correct magnetic field errors at varied gaps. Such mechanism is particular benefit for the cryogenic permanent magnet undulators because the field errors of undulator shall correct in both cryogenic mode and room temperature mode.